Obraz męki Chrystusa w XIX-wiecznych ulotnych drukach jarmarczno-odpustowych - Ratajczak, Tomasz (Archiwa, Biblioteki i Muzea Kościelne, 2011)
A few types of Passion prints were distributed at the markets and church fairs in Poland. Leaflets with narrative religious songs were among them and they are the ones which come under scrutiny in this text. The analysis of such prints with Passion songs, which were found in a few libraries, allows to state that the aim of these works was to remind Passion scenes which arose strong religious emotions. In these simple works, addressed to the commons, a strong emphasis was put on the humanity of characters as well as the human aspect of their experiences. (the key role in the description of the Passion was played by Mary, who shared sufferings of her Son). At the same time typical medieval means of representations were used in this form of work such as drastic scenes and moralizing tone, things which affected the uncomplicated mentality of the receivers and became embedded in the collective memory. Finally, these leaflets were characterized by the repetition of a general tendency of the medieval piety: subjectivism, realism and dolorism.